Effect of surface free energy of ceramic glaze on oil droplet shape and its behavior in water - 梁金生 孟军平 梁广川 王丽娟 张晋 李计元 (Transactions of Nonferrous Metals Society of China, 2006)
A super-hydrophilic functional ceramic was prepared by adjusting the chemical components of ceramic glaze. Effect of surface flee energy of ceramic glaze on oil droplet shape and its behavior in water were studied. The results show that water can spread on ceramic surface with high surface free energy, and oil droplet can aggregate rapidly and separate from the ceramic surface in water. For the ceramic with lower surface free energy, the polar shares are dependant on its easy-cleaning property. The higher the polar shares, the better the easy-cleaning property, and the easier the droplet separates from the ceramic surface in water.